(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article analyzes the existing technologies and technical means for basic tillage of the cotton-growing zone. Based on the analysis of technologies and technical means for the main tillage of the cotton-growing zone, it was found that improving the quality and stability of the technological process, reducing energy and labor costs when processing soils with low humidity can be achieved by developing a combined tillage tool, the working bodies of which would loosen the topsoil and plow in one pass. In such a combined unit, the working organs of passive and active action should be optimally combined.